Birth weight and family status revisited: evidence from Austrian register data - Wolfgang Frimmel; Gerald J. Pruckner (Johannes Kepler University of Linz, Department of Economics, 2011)
In this paper, we study the socio-economic determinants of birth weight with a focus on the mothers family status. We use Austrian birth register data covering all births between 1984 and 2007 and find that a mothers marriage is associated with a higher birth weight of the newborn in a range between 4 and 6 dekagrams. This result remains stable if we control for time-invariant unobserved mother heterogeneity. A divorce around pregnancy results in birth weight 2 to 8 dekagrams lower as compared to that of newborn babies of single mothers. The family status effects in the 2000s are stronger as they were in the 1980s. A quantile regression suggests that family effects are more pronounced at the lower quantiles of the birth weight distribution and diminish at higher percentiles. Finally, in accordance with several instrumental variable (IV) studies, we find that the significantly positive impact of family status on childrens health outcomes disappears if we confine our sample to mothers, who are below the age of 22 years. We conclude that social and financial stress may have an important influence on the birth weight of newborns, especially at the lower tail of the birth weight distribution.
Keywords: I12; J12; J13; C21; 330; Low birth weight; family status; newborn health; fixed-effects estimations; Körpergewicht; Kinder; Sozialer Status; Mütter; Österreich